Unveiling the Drivers of Financial Statement Fraud: The Roles of Financial Targets, Stability, External Pressures, Industry Traits, and Auditor Changes - Bahfen, Munirah; Komala, Lenda (Santoso Academy Network, 2025)
This research aims to determine the influence of Financial Targets, Financial Stability, External Pressure, Industry Characteristics, and Change of Auditor on Financial Report Fraud and its Review from an Islamic Perspective (Empirical Study on Food & Beverage Sub-Sector Companies Registered on the Indonesian Stock Exchange in 2018-2021) This research method uses quantitative research using secondary data in the form of Food&Bavarage Company Financial Reports from 2018 to 2021. The analysis used is a hypothesis with multiple linear regression data analysis methods. The results of this research show that the External Pressure variable influences financial report fraud. Meanwhile, the variables of Financial Target, Financial Stability, Industry Nature and Change of Auditor do not affect Financial Report Fraud. Managerial implications suggest that organizations should implement robust internal controls and governance frameworks to mitigate the risk of financial fraud. By closely monitoring financial targets and stability, managing external pressures effectively, understanding industry-specific risks, and ensuring the continuity and integrity of auditor relationships, companies can significantly reduce the likelihood of fraudulent financial reporting.